2022
DOI: 10.5334/aogh.3698
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Practice Nursing Roles, Regulation, Education, and Practice: A Global Study

Abstract: Background and Objectives: Several subgroups of the International Council of Nurses Nurse Practitioner/Advanced Practice Nurse Network (ICN NP/APNN) have periodically analyzed APN (nurse practitioner and clinical nurse specialist) development around the world. The primary objective of this study was to describe the global status of APN practice regarding scope of practice, education, regulation, and practice climate. An additional objective was to look for gaps in these same areas of role developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 16 publications
(17 reference statements)
2
23
0
Order By: Relevance
“…As previous research has shown and this study confirms, there is significant variation in the education requirements for ANP and APN (Beauchesne et al, 2020; Heale & Rieck Buckley, 2015; Kim et al, 2021; Pulcini et al, 2010; Wheeler et al, 2022; Zug et al, 2016). This study found that APN roles in the majority of participating LICs and LMICs did not meet all the educational requirements of the ICN APN guidelines, mainly being at master's level or above.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…As previous research has shown and this study confirms, there is significant variation in the education requirements for ANP and APN (Beauchesne et al, 2020; Heale & Rieck Buckley, 2015; Kim et al, 2021; Pulcini et al, 2010; Wheeler et al, 2022; Zug et al, 2016). This study found that APN roles in the majority of participating LICs and LMICs did not meet all the educational requirements of the ICN APN guidelines, mainly being at master's level or above.…”
Section: Discussionsupporting
confidence: 84%
“…Again, this variation of characteristics present may indicate the need for further education to address potential gaps in service. This variation has been described in other global studies (Heale & Rieck Buckley, 2015;Kim et al, 2021;Pulcini et al, 2010;Wheeler et al, 2022;Zug et al, 2016).…”
Section: Regulatory Mechanismssupporting
confidence: 78%
See 2 more Smart Citations
“…Students who graduate from nursing programs will have more opportunities than ever to work in international health settings. Appropriately prepared nurses will be able to meet the increasing global demand for quality health care (Rosa et al, 2021; Wheeler et al, 2022). All nurses will provide global health care regardless of where they practice.…”
Section: Introductionmentioning
confidence: 99%